Comparison of mortality in patients on chemotherapy or immunotherapy during and before the COVID-19 pandemic. Multicenter matched cohort study in Argentina - Boris Itkin; Samanta Straminsky; Hernán Cáceres; Mariana Onassis; Agustín Emilio García; Laura Avanzi; Lucia Kaminszczik; Richard Serna Sejas; Mara Rapaccioli; Gustavo Billordo; Damián Lavaccara; Julián Lanzavecchia; et al. (Revista Peruana de Medicina Experimental y Salud Pública, 2023)
Objectives. To compare the mortality of unvaccinated oncology patients who received chemotherapy or immunotherapy during the pandemic with those treated before the pandemic. Materials and methods. We conducted a cohort study in four tertiary hospitals in Argentina. Outpatients with a solid neoplasm of any stage on cytotoxic or intravenous immune therapy were eligible. The pandemic cohort was enrolled during the initial phase of the outbreak and compared with a cohort from a pre-pandemic period using propensity score matching (PSM). Subjects were matched for age, sex, health insurance, severe COVID-19 complications risk, performance status, cancer and treatment type, treatment line, and body mass index. All-cause mortality was estimated in both cohorts after the 6-month follow-up. Results. Out of 169 patients recruited between April and August 2020 to the pandemic and 377 to the pre-pandemic cohorts in the same period of 2019, 168 were matched. After PSM, all-cause mortality was 17.9% in the pandemic and 18.5% in the pre-pandemic cohort, Risk Ratio: 0.97 (95% confidence interval: 0.61-1.52, p=0.888). In the pandemic cohort, 30/168 patients died - none of them from COVID-19 infection. Conclusions. We failed to demonstrate an increment in the mortality of unvaccinated, ambulatory patients on active intravenous anticancer treatment exposed to the COVID-19 pandemic.